HIV Infection and Host Genetic Mutation among Injecting Drug-users of Northeastern States of India (Journal of Health, Population and Nutrition, 2010)
A community-based cross-sectional study was conducted among injecting drug-users (IDUs) of the northeastern states of India to understand the host genetic factors that confer resistance to HIV infection. The study aimed at assessing the existence and magnitude of genetic mutations of chemokine receptors, such as CCR2-64I, CCR-5 D-32, and SDF-1-3`A, that are known to confer resistance to HIV infection and progression of disease in some set-ups. In total, 711 IDUs from Manipur, Mizoram, Nagaland, and Meghalaya were sampled for the study. The selected participants were interviewed to study their sociodemography, risk behaviours, and risk perceptions after obtaining their verbal informed consent. The interview was followed by collection of about 5 mL of blood samples by an unlinked anonymous method for studying genetic mutation and HIV infection. All the blood samples were transported to and processed at the clinical medicine laboratory of the National Institute of Cholera & Enteric Diseases, Kolkata, India. The genetic mutations were detected by polymerase chain reaction (PCR) and the restriction fragment length polymorphism (RFLP) assay techniques. The study revealed that 328 (46.1%) IDUs were aged 20-29 years, 305 (42.9%) were aged 30-39 years, and only two (0.3%) were aged above 49 years. The rate of HIV seropositivity varied widely among the IDUs living in different northeastern states that ranged from 4.5% to 61%. There was not a single IDU with CCR5 homozygous mutation. Mutated genes of CCR2-64I and SDF-1-3'A were detected in the frequencies of 49% and 23% respectively in them. The rate of HIV seropositivity in IDUs having CCR2 mutant gene was 27% (n=94) and without mutation was 27% (n=98). Similarly, HIV seropositivity in IDUs with and without SDF1 mutation was 28% (n=46) and 27% (n=146) respectively. Both the differences were not statistically significant. A CCR5 homozygous mutation is known to be the most prominent marker that confers resistance against HIV infection. The absence of CCR5 mutant gene in this population suggests that they do not have any additional protection against HIV infection. Analysis also revealed that, although mutation of CCR2 and SDF1 was present in this population, it did not confer any additional resistance against HIV. This indicates that the IDUs of northeastern India are not additionally protected against HIV infection through genetic mutation and are, therefore, vulnerable to acquire HIV infection due to high-risk behaviour and other related factors. Key words: Community-based studies; Cross-sectional studies; Genetic mutation; HIV infections; Sexually transmitted diseases; Substrance-use; India DOI: 10.3329/jhpn.v28i2.4882 J Health Popul Nutr 2010 Apr; 28(2): 130-136